Actitudes del profesorado ante la educación de las alumnas de altas capacidades - Bueno Villaverde, Ángeles (FAISCA: Journal of High Abilities, 2006)
Teachers’ attitudes, beliefs and thinking towards gender education and giftedness are analyzed in this article. The answers given in a questionnaire, applied to teachers that participated in an educational project designed to improve the teaching of high ability students, are investigated.
Keywords: Intellectual giftedness; Women; Teachers’ attitudes; Attitudes towards women